1999
DOI: 10.1897/1551-5028(1999)018<2545:ocimfh>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine Contaminants in Mummichog(fundulus Heteroclitus) Living Downstream From a Bleached-Kraft Pulp Mill in the Miramichi Estuary, New Brunswick, Canada

Abstract: Abstract-Mummichog, a small-sized sentinel fish species, has been proposed for use in environmental effects monitoring programs conducted by pulp mills that release their effluent in marine waters. In order to evaluate the suitability of mummichog as a sentinel species and to support the interpretation of biological effects data, tissue concentrations of polychlorinated dibenzo-p-dioxins and dibenzofurans, (PCDD/Fs), chlorophenolic compounds (CPs), polychlorinated biphenyls (PCBs), and chlorinated pesticides w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Filtered ambient seawater (salinity $26 PSU) was provided by the Maurice Lamontagne Institute marine laboratory system, located on the south shore of the St. Lawrence Estuary, QC. Previous measurements of PCBs, polychlorinated dibenzodioxins and dibenzofurans in the liver of mummichog captured at Horton's Creek indicated low contamination and supported the selection of this site as a reference (Couillard and Nellis, 1999). To induce gonadal maturation, the water temperature was raised progressively from 10°C to 20°C, and a photoperiod of 14-h light: 10-h dark was maintained (Boyd and Simmonds, 1974;Couillard, 2002).…”
Section: Source Of Mummichog Larvaementioning
confidence: 88%
“…Filtered ambient seawater (salinity $26 PSU) was provided by the Maurice Lamontagne Institute marine laboratory system, located on the south shore of the St. Lawrence Estuary, QC. Previous measurements of PCBs, polychlorinated dibenzodioxins and dibenzofurans in the liver of mummichog captured at Horton's Creek indicated low contamination and supported the selection of this site as a reference (Couillard and Nellis, 1999). To induce gonadal maturation, the water temperature was raised progressively from 10°C to 20°C, and a photoperiod of 14-h light: 10-h dark was maintained (Boyd and Simmonds, 1974;Couillard, 2002).…”
Section: Source Of Mummichog Larvaementioning
confidence: 88%
“…Spawning asynchrony with the lunar cycle for the northern subspecies in this study suggests another environmental cue is probably acting as the primary synchronizer as suggested by Wallace & Selman (1981) in Woods Hole, Massachusetts. Because of a positive correlation between water temperature and I G ( P < 0·001; r = 0·62), which is consistent with the findings in other northern studies (Newman, 1907; Wallace & Selman, 1981; Couillard & Nellis, 1999), the spawning processes of the F. h. macrolepidotus appears to be largely temperature dependent. Photoperiod, however, can be considered as well, considering the influence of longer daylight hours on water temperature and the co‐occurrence of peak spawning period with the summer solstice which is the longest period of daylight hours in the northern hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from the New Jersey area have reported varying results compared with more northern studies in terms of reproductive timing (Taylor, 1984). Interestingly, several northern studies have concluded different results than expected in reproductive rhythm when comparison is made with control groups (Leblanc et al , 1997; Couillard & Nellis, 1999; Thériault et al , 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Tomcods from the SLE have higher percentages of tetrachloro‐substituted PCBs compared with tomcods from the ME and RE. In the SLE, most PCBs likely originate from distant industrial sources located on the shores of the upstream SL River or Lake Ontario, whereas local industrial sources may be the main source of contamination in the ME [25]. Enrichment in lighter PCB congeners is expected to occur as distance from the source increases [11].…”
Section: Discussionmentioning
confidence: 99%